New Echinoid (Spatangoida: Toxasterinidae) from the Campanian of Coahuila, Northeastern Mexico - Silva Martínez, Luis Encarnación; Blanco Piñón, Alberto; De León González, Jesús Ángel; Rodríguez Vela, Hidalgo (Sociedad Geológica Mexicana, 2016)
ABSTRACT Three specimens corresponding to a new echinoid species from the Upper Cretaceous (Lower Campanian) from Austin Formation in the northeastern of Mexico are reported here. The morphology of the specimens (test with a cordiform aboral region) as well as the sedimentary environment reported at the Austin Formation, suggests that this species represents an infaunal and detritivorous dweller living in a shallow water environment within the continental shelf. This is consistent with the more actual knowledge for other species of Diplodetus Keywords: Echinoids, Diplodetus, Upper Cretaceous, Campanian, Austin Formation, NE Mexico.